2018
DOI: 10.1016/j.jped.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for central venous catheter-related infections in a neonatal population – systematic review

Abstract: Catheter-related bloodstream infections still show high incidence density rates in developing countries. The authors emphasize the need for further longitudinal studies and the need for better strategies to prevent risk factors, aiming at the reduction of catheter-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
7
1
4
Order By: Relevance
“…Os resultados evidenciaram ainda elevado percentual (41,1%) de complicações relacionadas ao cuidado (3) . Uma pesquisa realizada em uma UTI neonatal de um hospital universitário encontrou obstrução em 17% dos 52 PICCs implantados em RN, seguido de infiltração em 12% (8) . Vale salientar que diferentes estudos apontam dados consideráveis para a retirada precoce do PICC associada à ruptura (10)(11)(12)(13)(14) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os resultados evidenciaram ainda elevado percentual (41,1%) de complicações relacionadas ao cuidado (3) . Uma pesquisa realizada em uma UTI neonatal de um hospital universitário encontrou obstrução em 17% dos 52 PICCs implantados em RN, seguido de infiltração em 12% (8) . Vale salientar que diferentes estudos apontam dados consideráveis para a retirada precoce do PICC associada à ruptura (10)(11)(12)(13)(14) .…”
Section: Discussionunclassified
“…Embora o uso de dispositivos venosos seja de extrema importância no cuidado neonatal, existe risco de eventos adversos relacionados aos dispositivos, tais como obstrução mecânica do PICC e infecção associada aos cateteres inseridos cirurgicamente, sendo a mais frequente a sepse clínica (8) . Mesmo com a ocorrência de eventos adversos, o uso desses dispositivos venosos é fundamental para a melhora do quadro clínico do paciente.…”
Section: Introdução Métodounclassified
“…The insertion of peripherally inserted central catheters (PICC) is common in neonatal intensive care units (NICU) in term newborns (NBs) and premature infants receiving venous therapies with vesicant and irritating drugs and parenteral nutrition. Moreover, depending on the caliber, it is also used for blood tests, transfusion of blood products, and hemodynamic monitoring [1,2]. These reduce the risk of complications and dispense with the need for surgical intervention, which is advantageous due to the reduced hospitalization time, reduced hospital costs, and decreased incidence of neonatal mortality, as PICC reduce the incidence of complications when compared to other central catheters [3].…”
Section: Introductionmentioning
confidence: 99%
“…Premature NBs generally have low birth weight, and many are dependent on hyperosmotic or irritating drugs, which must be administered through a long-term venous access [2]. Previous studies have identified risk factors for complications associated with the use of PICC in NBs, including gestational age (GA), catheter insertion location, catheter tip location, and catheter dwell time, especially when it is installed for greater than 35 days, a factor also associated with an increased catheter-related bloodstream infection [1,4]. Other mechanical complications appear with a lower incidence such as rupture of the catheter, migration of the catheter tip, obstruction, and leakage of drugs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…O tipo de cateter a ser adotado irá depender do propósito da conduta clínica, da durabilidade do tratamento, assim como da finalidade desse. O uso do Cateter Venoso Central de Inserção Periférica (PICC) versa sobre uma técnica de acesso venoso duradouro e seguro (3) .…”
Section: Introductionunclassified